In vitro evaluation of sunscreens in the context of extreme UV indexes in Lima-Peru - Villareyes, Eduardo (2024)
Currently in Peru, UV index levels exceed the maximum allowable value (11+ Extreme). For this reason, it is important to evaluate the effectiveness of sunscreens with different Sun Protection Factor (SPF) ratings, which is a laboratory measure of the sunscreen's efficacy against UV-B radiation on our skin. In this study, the in vitro technique will be used following COLIPA recommendations, which involves measuring the transmission of UV radiation through the cream. The results obtained for the different SPFs are consistent with the values indicated on the product packaging: Bahía-SPF 45, Avon-SPF 50, and Bahía-SPF 70. However, they deviate by 30% from the indicated values for the higher SPFs, specifically Bahía-SPF 90, Bahía-SPF 100, and Unique-SPF 100